Influence of the overall stiffness of a load-bearing porous titanium implant on bone ingrowth in critical-size mandibular bone defects in sheep. (June 2016) - Schouman, T.; Schmitt, M.; Adam, C.; Dubois, G.; Rouch, P.
Abstract: The aim of this work was to assess the influence of reduction of the apparent mechanical properties of fully load-bearing porous titanium implants used in mandibular bone defects. Segmental 18 mm long bone defects were created bilaterally in the lower jaws of adult ewes. One group of 6 ewes (group A) was treated with load-bearing 'rigid' (high stiffness) porous implants on the right side, and with control on the left side. A second group of 6 ewes (group B) was treated with 'flexible' porous and control implants exhibiting apparent mechanical properties ten times lower than the rigid implants. The mechanical behavior of the reconstructed hemi-mandibles was assessed by cantilever testing and bone ingrowth into the segmental defects was assessed by BV/TV measurement within the implant using micro-CT 12 weeks after implantation. A significantly higher rigidity was identified for porous implants compared with control implants at the anterior interface in group B. BV/TV of porous implants was significantly higher than that of control implants in group A. BV/TV differences were significant between porous and control implants in group B and were homogeneous along the main axis. Significantly higher BV/TV was identified in most sub-volumes of group B porous implants compared with group A. This work highlights the critical importance of the tuning of scaffolds to promote bone ingrowth with reference to the local strains occurring within the porous scaffold, which in this application was achieved using fully load-bearing low-stiffness porous titanium implants.